Endoribonucleolytic Cleavage of m6A-Containing RNAs by RNase P/MRP Complex - Park, Ok Hyun; Ha, Hongseok; Lee, Yujin; Boo, Sung Ho; Kwon, Do Hoon; Song, Hyun Kyu; Kim, Yoon Ki (Molecular cell, 2019)
N6-methyladenosine (m6A) is the most abundant internal modification in RNAs and plays regulatory roles in a variety of biological and physiological processes. Despite its important roles, the molecular mechanism underlying m6A-mediated gene regulation is poorly understood. Here, we show that m6A-containing RNAs are subject to endoribonucleolytic cleavage via YTHDF2 (m6A reader protein), HRSP12 (adaptor protein), and RNase P/MRP (endoribonucleases). We demonstrate that HRSP12 functions as an adaptor to bridge YTHDF2 and RNase P/MRP, eliciting rapid degradation of YTHDF2-bound RNAs. Transcriptome-wide analyses show that m6A RNAs that are preferentially targeted for endoribonucleolytic cleavage have an HRSP12-binding site and a RNase P/MRP-directed cleavage site upstream and downstream of the YTHDF2-binding site, respectively. We also find that a subset of m6A-containing circular RNAs associates with YTHDF2 in an HRSP12-dependent manner and is selectively downregulated by RNase P/MRP. Thus, our data expand the known functions of RNase P/MRP to endoribonucleolytic cleavage of m6A RNAs. [Display omitted] •m6A-containing RNAs are degraded by an endoribonucleolytic cleavage pathway•A YTHDF2-HRSP12-RNase P/MRP axis contributes to m6A-mediated RNA decay•An interaction between YTHDF2 and RNase P/MRP is bridged by HRSP12•m6A-containing circular RNAs are degraded by the YTHDF2-HRSP12-RNase P/MRP pathway m6A-containing RNAs are known to be recognized and destabilized by YTHDF2. However, the underlying molecular mechanisms remain unclear. Park et al. show that m6A-containing linear and circular RNAs are endoribonucleolytically cleaved by a YTHDF2-HRSP12-RNase P/MRP axis.